Educação patrimonial: a construção de material didático a partir do patrimônio cultural de Santo Ângelo - Oliveira, Felipe Ferraz de (2023)
This paper deals with heritage education based on memory spaces and monuments in the town of Santo Ângelo in Rio Grande do Sul State. The research is organized around the following investigative question: how to prepare a study guide that is a history teaching tool in Santo Ângelo, for the mediation of heritage education? The purpose is developing a study guide as a way of enabling the construction of historical knowledge about local history. For structuring this paper, firstly, it is seeking to build up a theoretical framework with concepts about heritage education, memory, as well as the historical context of the town of Santo Ângelo. Secondly, a study guide is prepared to assist Basic Education students and teachers as a teaching tool about and to preservation of memory and local and regional history of the town of Santo Ângelo. Therefore, it is concluded that the paper proposal with heritage education could enable the construction of historical knowledge that is significant in the students’ trajectory.